Involvement of the CX3CL1 (fractalkine)/CX3CR1 pathway in the pathogenesis of acute graft‐versus‐host disease. Issue 2 (24th November 2014) - Brissot, Eolia; Bossard, Celine; Malard, Florent; Braudeau, Ce´cile; Chevallier, Patrice; Guillaume, Thierry; Delaunay, Jacques; Josien, Re´gis; Gregoire, Marc; Gaugler, Beatrice; Mohty, Mohamad
Abstract : The implication of the CX3CL1/CX3CR1 axis in the pathogenesis of acute graft‐versus‐host disease. Abstract : This study investigated the role of cytokines and chemokines in aGVHD incidence and severity in 109 patients who underwent reduced‐intensity conditioning allogeneic stem cell transplantation (HSCT). Among the 42 cytokines tested at d 0 HSCT, only CX3CL1 levels at d 0 HSCT were significantly associated with Grades II–IV aGVHD development ( P = 0.04). Increased levels of CX3CL1 at d 20–30 and 50 post‐HSCT were also significantly associated with aGVHD ( P = 0.02 and P = 0.03, respectively). No such association was found before the conditioning regimen or at d 100–120 post‐HSCT. As the receptor for CX3CL1 is CX3CR1, the number of CX3CR1 + cells was determined by flow cytometry. The CX3CR1 + CD8 + T cell proportion was significantly higher in patients with aGVHD than those without aGVHD ( P = 0.01). To investigate the distribution of the CX3CL1/CX3CR1 axis in the anatomic sites of aGVHD, CX3CL1 and CX3CR1 levels were studied by use of an in situ immunohistochemical analysis on GI biopsies of patients with intestinal aGVHD. CX3CL1 expression was increased significantly in the epithelial cells and mononuclear cells of the lamina propria. CX3CR1 + mononuclear cells were identified in close contact with epithelial cells. These findings strongly suggest the implication of the CX3CL1/CX3CR1 axis in the pathogenesis of aGVHD.